Mencegah Kenakalan Remaja dan Narkotika Melalui Penyuluhan Hukum bagi Siswa- Siswi Remaja SMKN 6 Kecamatan Kasemen Kota Serang - Rizki Prasetio; Muhammad Rama Ramadhan; Siti Salbiyah; Rahuldi Rahuldi; Ulinnuha Ulinnuha (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Juvenile delinquency and the dangers of narcotics among secondary school children are social phenomena that must be immediately addressed together. Juvenile delinquency that often occurs nowadays seems to have lost its indication of delinquency and has led to criminal acts that can endanger the safety and comfort of people's lives. In this regard, the Bina Bangsa University PkM team has a program for implementing community service to provide solutions to the problem of juvenile delinquency and narcotics in the Kasemen District area which is rampant and never resolved. This service program takes the form of legal counseling to prevent and combat juvenile delinquency and narcotics abuse. Thus, there are several stages that constitute the method of implementing community service, namely, the observation stage, the preparation stage, the implementation stage and the evaluation stage. The results of these legal counseling activities are that the PkM Program at Bina Bangsa University has had a positive impact and significant results on the legal awareness of teenagers in Kasemen District, especially students at SMKN 6 Serang City. Providing counseling about literacy and the dangers of narcotics provides benefits, insight and experience. new for partners to fight the influence of narcotics, providing education regarding the indications and losses of juvenile delinquency, providing legal awareness for partners not to engage in deviant juvenile delinquent behavior. PkM activities, which take the form of legal counseling to educate Kasemen teenagers so they can fight the influence of narcotics and juvenile delinquency, can minimize crucial legal problems in the Kasemen District which are rampant.